Transformative Learning and Cultural Capabilities: Understanding Factors Associated with Student Preparedness to Work with Indigenous People in Health Settings - Bullen , Jonathan Craig (Curtin University, 2019)
Indigenous Studies health curriculum has the potential to transform attitudes, behaviours and beliefs of non-Indigenous Australian students. This mixed methods research comprising five publications, and framed by Mezirow’s transformative learning theory, explored the pedagogical, personal and contextual factors of this complex learning environment. Findings support transformative learning experiences as a mechanism for changing attitudes and increasing preparedness to work in Indigenous health settings, with implications for future Indigenous Studies curriculum and educator development.